Constraints in Adoption of Mung bean Production Technology - Singh, Bhagwan; Chauhan, T R (Annals of Arid Zone, 2016)
The study was conducted in six villages of Jodhpur district of Rajasthan. From each village 30 mung bean growers were randomly selected. Thus total sample size was 180. Data were collected with the help of structured schedule through personal interview. Study revealed that major constraints perceived by the different categories of farmers were non-availability of high yielding varieties at proper time, lack of knowledge about the practices, lack of moisture in the field, lack of improved implements, lack of organic manure, lack of irrigation facilities, labor problem, high cost of inputs (seed, fertilizer and pesticides), lack of technical guidance and lack of finance. The study suggests that there is a need of educating the farmers about improved practices and supply of required input to them on reasonable cost at proper time to boost up the production of mung bean in arid areas of Rajasthan. Key words: Mung bean, constraints, high yielding varieties, plant protection measures.